THE EFFECTIVENESS OF THE TAKE AND GIVE MODEL ASSISTED BY FLASHCARD MEDIA ON IPS LEARNING RESULTS - Khoirul Muna, Nala; Widihastrini, Florentina; Setyasto, Novi (Universitas Negeri Semarang, 2019)
The objectives of this research were: 1) to describe the learning outcomes of 4th grade students in elementary school of the Ikan Mas Cluster, North Semarang; 2) to describe the activities of 4th grade students in elementary school of the Ikan Mas Cluster, North Semarang; 3) to analyze the effectiveness of take and give model assisted flashcard on social studies learning outcomes. Based on interview, documentation, and observation,it was found that social studies learning outcomes were not optimal because the lack of learning model variation and facilities. Direct Instruction model made students believe that the teacher will explain all the material that they have to know. The population of this study amounted to 163 students. The samples used Kuningan 02 elementary school as control class with 39 students and Kuningan 03 elementary school as experimental class with 25 studens in 2019/2020 school year. The result showed experimental group had better result compared to control group in grades and activeness score respectively. The experimental group had higher grades (76,10) than the control group (61,30). The activeness score of the experimental group was higher (75%) than the control group (59%). Both, grades and student's activeness of experimental group were higher than control group.Hypothesis test results showed that tcount ttable (3.0462 1.9990), which meant Take and Give model assisted by flashcard media was more effective on the social studies learning outcomes of 4th grade students. The conclusion of this research was that Take and Give learning model assisted by flashcard media was effectively used in social studies learning material of Hindu, Buddha, and Islam Kingdoms in Indonesia than Direct Instrucruon model and could improve learning outcomes and activities of4th grade students of the Ikan Mas Cluster, North Semarang.